Social discounting rate is negatively correlated with fluid intelligence - Osiński, Jerzy; Ostaszewski, Paweł; Karbowski, Adam (Personality and individual differences, 2014)
The purpose of the study was to verify a hypothesis, inspired by the handicap principle, of a positive relationship between subjective value of a hypothetical monetary reward shared with others and the level of fluid intelligence. Manipulation involved the amount of reward to be shared (small vs. large amount) and subject's relationship to recipients (related vs. unrelated). As expected, a positive correlation was found between the subjective value of a reward to be shared with others, measured as the area under the curve for the discounting function and Raven Advanced Progressive Matrices scores, but the relationship was only present for rewards shared with relatives. In addition, participants who made altruistic choices in all items scored higher in RPM than those who were not as consistent. The implications of results for the evolutionary interpretation of the relationship between intelligence and altruism are discussed.